An update on CCAFS LED Activities funded by USAID - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
An update on CCAFS LED Activities funded by USAID, presentation by Lini Wollenberg, Low Emissions Development Flagship Leader at USAID offices in Washington September 24 2018